Borinic Acid‐Catalyzed Regioselective Ring‐Opening of 3, 4‐ and 2, 3‐Epoxy Alcohols with Halides. Issue 2 (17th December 2019) - Wang, Grace; Taylor, Mark S.
Abstract: Methods for the regioselective ring‐opening of 3, 4‐epoxy alcohols and 2, 3‐epoxy alcohols with halide nucleophiles, using a diarylborinic acid catalyst, are disclosed. Ring‐opening occurs at the position proximal to the OH group, an effect ascribed to a catalytic tethering mechanism whereby coordination to the substrate OH group positions the diarylborinic acid to deliver a coordinated halide nucleophile. These methods provide access to halohydrin substitution patterns that were not previously accessible through catalytic epoxide ring‐opening reactions. Abstract :